New Polish Theatre on the Small Screen: the TV series Artyści (Artists, 2015) - Baluch, Wojciech (Przestrzenie Teorii, 2023)
The article describes the phenomenon of the Polish TV series Artists. Created by the theater creators Strzępka and Demirski were their TV debut. The series has become iconic among the theater community. Analyzing the series I show its sources, which are stuck in the extraordinary recent development of Polish theater dramaturgy . I also try to show how the series opens the directing to new dimensions of creativity. The changes that have taken place in the Polish theater allow to replace the dominant models of affirmation and subversion with an affective approach to art whose frame I become experience.